Labour and Employment Policy: Opportunities and Challenges for Undergraduate Students - Mariam Davitadze (European Scientific Journal, ESJ, 2023)
The purpose of the study is to identify specific needs that will contribute to the employment opportunities of undergraduate students in the workplace with appropriate conditions. The presented article discusses the mechanisms of employment and promotion of undergraduate students, which, on the one hand, will improve the socio-economic status of students, and on the other hand, will help them combine work and study. Based on the review of the international literature and as a result of the conducted quantitative research, the circumstances and features promoting the employment of students were studied, the challenges faced by undergraduate students in Georgia during employment were analyzed and identified. As a result of the obtained data, such hindering circumstances of employment were determined, such as unsuitable work schedule, lack of student work in the labour market, low interest of employers in employing students, wages and working hours. Based on the sources, approaches, practices and mechanisms in the world focused on the promotion of student employment, which in itself improves the socio-economic status of students and increases their motivation to study, have been identified. The article presents the advantages and disadvantages of mechanisms promoting the employment of undergraduate students and generalizes them in relation to the existing international practice. The focus is on the lack of student jobs in the labour market, access problems and their causes. The subject of the research is the state policy of promoting the employment of undergraduate students, and the object of the research is current undergraduate students of private and state educational institutions of the Autonomous Republic of Ajara. The main task of the work is to study the attitudes of students, educational institutions and employers towards the employment of students in jobs with appropriate working conditions, to identify gaps and develop recommendations. Research methods such as analysis and synthesis, systematic, inductive-deductive, statistical and comparative-legal were used in the research process. As a result of the research, it was determined that the system cannot respond to the challenges related to student employment.